Pengaruh Brand Image, Harga, Lokasi, Kualitas Produk Dan Word Of Mouth Terhadap Keputusan Pembelian Es Teh Poci Di Tempurejo Jember - Maya Ursila; M. Dimyati; Haifa (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the influence of Brand Image, Price, Location, Product Quality, and Word Of Mouth on the purchasing decision of Es Teh Poci in Tempurejo Jember. This research is a type of quantitative research. The population in this study is Consumers of Es Teh Poci in Tempurejo Jember. The sample used was 60 respondents. The sampling technique used was Purposive sampling. The data analysis method used multiple linear regression with the help of IBM SPSS Statistics 20. The tests used were data instrument tests (validity tests and reliability tests), classical assumption tests (normality tests, multicollinearity tests, heteroscedasticity tests), t tests and F tests. the results of this study indicate that Brand Image, Product Quality, and Word Of Mouth partially have no significant influence on Purchasing Decisions, while Price and Location partially have a significant influence on Purchasing Decisions. Simultaneously, Brand Image, Price, Location, Product Quality, and Word Of Mouth have a significant influence on Purchasing Decisions of Es Teh Poci in Tempurejo Jember.